IMPLEMENTASI KURIKULUM MERDEKA BELAJAR DALAM PEMBELAJARAN PENDIDIKAN AGAMA HINDU DAN BUDI PEKERTI PADA SISWA KELAS V SD NEGERI 3 BONA KECAMATAN BLAHBATUH KABUPATEN GIANYAR - Trisnanda Putra, I Gusti Ngurah Agus; Anggreni, Ni Made; Ayu Septiari Dewi, Putu (Guna Widya: Jurnal Pendidikan Hindu, 2025)
The implementation of the Independent Learning Curriculum at SD Negeri 3 Bona still requires refinement to achieve optimal results, as not all students focus on the learning delivered through Quizizz media, thus necessitating further adjustments. The issues this paper looks at include: 1. How is the implementation of the Independent Learning Curriculum in Hindu Religious and Moral Education learning among fifth-grade students at SD Negeri 3 Bona? 2. What obstacles do educators and learners experience when putting the Independent Learning Curriculum into practice for Hindu Religious and Moral Education subjects in fifth grade at SD Negeri 3 Bona, and what steps are taken to address these constraints? 3. What are the implications of Hindu Religious and Moral Education learning in fifth grade at SD Negeri 3 Bona? In implementing the Merdeka Belajar Curriculum, the theories employed in this study are Behavioristic and Constructivistic theories. The research type utilized is qualitative with a phenomenological approach. Furthermore, the data sources employ both primary and secondary data. Primary data includes interviews and observations, while secondary data comprises journals, articles, and internet sources. The informant selection technique employed is purposive sampling. Data collection techniques utilize observation, semi-structured interviews, literature review, and documentation, which are then analyzed utilizing descriptive qualitative methods through data collection stages involving data reduction, data presentation, and construction of the conclusion. The research outcomes indicate that the implementation of the Independent Learning Curriculum through planning, execution, and evaluation encounters constraints, including difficulties in designing modules and lack of student discipline. These constraints can be addressed through teacher training, discipline enforcement, and optimization of learning media. The learning implications are evident in students' cognitive, affective, and psychomotor domains. Keywords: Implementation, Independent Learning Curriculum, Hindu Religious Education and Character Development